1975
DOI: 10.2134/agronj1975.00021962006700040028x
|View full text |Cite
|
Sign up to set email alerts
|

Thatch Development and Other Effects of Preemergence Herbicides in Kentucky Bluegrass Turf1

Abstract: Preemergence herbicides have been used extensively on turf in recent years to prevent annual weed development. Applications of these herbicides have been suspected of causing reduced turfgrass quality. The purpose of this study was to determine whether repeated use of preemergence herbicides resulted in thatch development and other effects associated with turfgrass deterioration. Six preemergence herbicides were applied annually for 4 years to ‘Kenblue’‐type Kentucky bluegrass (Poa pratensis L.) growing on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
3
17
0
Order By: Relevance
“…However, until the ecological role of ori- batid mites and other microarthropods in turfgrass is better understood, it is impossible to know if those changes could affect the rate of thatch decomposition. Other investigators have reported increases in thatch when earthworm populations were reduced by application of certain insecticides and herbicides (Randell et al, 1972;Turgeon et al, 1975). In the present study, earthworms were significantly less abundant in the fertilized turf.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…However, until the ecological role of ori- batid mites and other microarthropods in turfgrass is better understood, it is impossible to know if those changes could affect the rate of thatch decomposition. Other investigators have reported increases in thatch when earthworm populations were reduced by application of certain insecticides and herbicides (Randell et al, 1972;Turgeon et al, 1975). In the present study, earthworms were significantly less abundant in the fertilized turf.…”
Section: Resultssupporting
confidence: 48%
“…Although a number of studies have indicated correlation between high rates of fertilization and thatch accumulation (Starkey, 1953;Engel and Alderfer, 1967;Meinhold et al, 1973;Smith, 1978), there is evidence that this may not always occur (Turgeon, 1979;Shearman et al, 1980). Shearman et al ( 1980) suggested that other conditions may have to be present for N-ind~Jced thatch accumulation to oq:ur.…”
Section: Resultsmentioning
confidence: 99%
“…Judging by the responses of annual bluegrass, crabgrass, and bentgrass in our study (Tables 2, 3, and 4), the initial high soil P level did not diminish the effect of arsenic toxicity, just as was shown by Carrow et al (1975). Other researchers used very high single arsenic levels, ranging from 209 to 683 kg·ha -1 (Hall et al, 1974;Juska, 1961;Turgeon et al, 1974Turgeon et al, , 1975. In this study, very low increment levels of 17 or 34 kg·ha -1 were used with gradual accumulations over 4 years totaling a maximum of 272 kg· ha -1 .…”
Section: Resultssupporting
confidence: 63%
“…since Ca-Ars functions also as an insecticide. In a subsequent study, Turgeon et al (1975) showed significant thatch increases in a 'Kenblue' Kentucky bluegrass lawn following four annual applications of Ca-Ars at 439 kg·ha -1 . Again, thatch accumulation was associated with a complete lack of earthworms.…”
mentioning
confidence: 93%
“…Through superior competition during spring and fall, annual bluegrass weakens the perennial turfgrasses and becomes dominant (Brede and Duich 1986 (Bingham et al 1969), but have been used less often on golf course fairways because of injury at high rates (Turgeon et al 1975) and their ineffectiveness in Can. J.…”
mentioning
confidence: 99%